Independence of judiciary and the appointment of judges - Prem Kumar; Bhatia, Raj (1999)
Examining in detail the concept of independence of judiciary, the authors analyse opinions of judges as well as academics, society's expectations from judges and views on their qualities from Puranic Times, methods of their appointment with Law Commission's recommendations. They move on to analyse judiciary's independence in the present context on the basis of Supreme Court judgements which consider it a basic central value. They also draw support to this view from pre-Constitution days, existing Constitutional provisions, and the vital change that has set in since decisions on the First Judges Case and the Second Judges Case and the controversy regarding primacy of Chief Justice of India in matters of appointment and transfer of judges. Also covering in the discussion the remedies suggested by different quarters - need for a Collegium and National Judicial Commission - they conclude by raising the question regarding the desirability of change in the existing arrangement. - Reproduced
Keywords: Judges - India; Judiciary - India; Judiciary